Talfiqat al-Masabih fi SharhMasabihal-Sunna by Muhammad ibn Muhammad al-Izniqi al-Rumi al-HanafiQutb al-Din Zadah (d. 821 AH), with the Chapter on Faith as a Case Study:A Study, Critical Edition, and Commentary - Osama AyadJaafar,; Muhannad Abdul SattarJameel, (Islamic Sciences Journal, 2025)
This study examines the manuscript Talfiqatal-Masabih fi SharhMasabih al-Sunnah by Sheikh Muhammad ibn Muhammad al-Izniqi al-Rumi al-HanafiQutb al-Din Zadeh (d. 885 AH), focusing on its critical investigation and hadith-based analysis. The research highlights the manuscript’s scientific value, which includes hadith-related benefits and scholarly rules for resolving apparent contradictions in the hadith texts of Masabih al-Sunnah by al-Baghawi. The study also explores the author’s biography, academic life, teachers, students, and his diverse contributions to Islamic sciences. The term talfiqat is analyzed linguistically and terminologically, emphasizing its role in harmonizing seemingly conflicting hadiths. The study concludes that the manuscript is a significant addition to Islamic literature, bridging jurisprudence and Sufism, and reflects the author’s efforts in textual criticism and establishing scientific principles.